Hubungan Kebermaknaan Kerja melalui Keterlibatan Kerja pada Guru SD/MI - Lailatul Munawaroh; Devilia Candy Eka Yurisca; Nova Hexa Minung Jamila; Maulida Adhiyah (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2023)
This study aims to determine the meaning of work and work involvement of teachers in SD/MI. This study used a sample of 51 teachers from a total population of 98 teachers at SD Anak Saleh, SDIT Ahmad Yani and SD MISS. The data collection technique uses a questionnaire, while to analyze the data the researcher uses ANOVA. The results of this study indicate that there is a relationship between work engagement and the meaning of work with a coefficient of p = 0.000 R Square 361 with a percentage of 36.1%. Other aspects of the results of work engagement and the meaning of work are gender demographics, marital status, professional status and years of service.